Faktor yang Berhubungan dengan Perkembangan Motorik Balita di Wilayah Kerja Puskesmas Kampa Kabupaten Kampar Provinsi Riau - Erlinawati, Erlinawati; Apriza, Apriza; Parmin, Joria (Poltekkes Kemenkes Padang, 2023)
Toddlerhood is a critical period that determines the growth and development of children. According to UNICEF in 2015, the number of motor development disorders in children was 3 million (27.5%). The results of the 2012 SDKI showed that the number of early childhood (0-6 years) was 26.1 million, about 14.1 per cent had developmental delays. Based on the results of monitoring in the Kampa Community Health Centre working area, Tanjung Berulak village is the village with the highest percentage of developmental delays in toddlers. The purpose of the study was to analyse the relationship between education, occupation, and parenting patterns of mothers with the development of mokorik toddlers in the working area of the Kampa puskesmas in Kampar district in 2022. This study used a cross sectional design. The population is all toddlers who have KMS. Samples were taken from a total population of 52 toddlers. The research location is in Tanjung Berulak village, Kampa health centre working area, Kampar Regency. Data analysis using Fisher's Exact statistical test. The results of the study showed a relationship between education, occupation, and parenting of mothers with motor development of toddlers in the Kampa Health Centre Working Area in 2022. It is expected that health workers can increase preventive efforts through health promotion for mothers of toddlers related to delays in motor development.